Muhammadiyah Education in Gempol Village during the Covid 19 Pandemic - Rahmad Kaosar Fatoni; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This research is to discuss the learning strategies that teachers do to students in imparting online or online learning at SMP Muhamadiyah 4 Gempol. Because the learning strategy is one aspect of successful learning for teachers. The learning strategy is a whole series of teaching material presentations which includes all aspects before and after learning by the teacher as well as all related facilities used directly or indirectly in the teaching and learning process. The purpose of this scientific article is to train students' abilities in environmental education, therefore we as students make observations of the SMP Muhamadiyah 4 Gempol school. The conclusion that I can take is that in the implementation of teaching and learning activities it is not always done face-to-face but can be done online as it is today due to conditions that do not allow face-to-face learning, but still it is the maximum effort for the teacher not to decide learning in school so that students continue to receive learning material